Comparison of Ultra Fine Grinding Effect on Gold Recovery Using Intensive Leach Test Method at PT Geoservices - Nailzidane Nefananda Dziban; Dyah Probowati (Proceeding of the International Conferences on Engineering Sciences, 2024)
Indonesia is an archipelagic country that has abundant mineral wealth, both metal minerals and other minerals. Metal minerals, including gold, tend to have a higher economic value. Based on data from the Ministry of Energy and Mineral Resources, the world's gold reserves in 2020 were 50,300 tons of Au. Indonesia is among the 5 largest in the world with 5% of the total gold reserves, which is 2,600 tons of Au. Therefore, it is necessary to develop technology and science in the mining industry, especially gold and silver, to improve the optimization of the process and increase the added value of the mining products themselves. One of the gold extraction processes can be done hydrometallurgically with the cyanidation method using a intensive leach test. The results of this experiment show that factors such as cyanide usage and ultra fine particle size will greatly affect the recovery of gold and silver metals.